PIMPINAN LEMBAGA PERGURUAN TINGGI KEAGAMAAN ISLAM (PTKI) VISIONER DAN ORIENTASI TOTAL QUALITY SEBAGAI LOKOMOTIF KESIAPAN PTKI DALAM MENYONGSONG MASYARAKAT EKONOMI ASEAN (MEA) - Aguswan Khotibul Umam (Pascasarjana IAIN Metro, 2016)
These days, the universities are required to be prepare of quality assurance in becoming ASEAN Economic Society. Therefore, the visionary leadership sense inside PTKI like structure, focus, recognize legality, communication, dinamic style, and responsive are needed to create the qualified PTKI. At least the qualified PTKI should have 8 factors such as scores and assignment, organization structure, communication, decision-making by agreement, and dinamic curriculum planning. Visionary leadership is vision based, which have the ability to face the reality and confidence in making people to be sure that the visions will be realize. The ability that should have by visionary leadership are: (a) capable in making good connection with staff and employment (in organization) who need guidance, support, and motivation; (b) capable in employing the external area maximally and have good relation with the outer which make the organization success; (c) capable in creating and influencing whole operation aspect of organization including the visions achievement, the quality of control system, the organization structure, and the information system; (d) capable and smart in dealing the future.